The Mediating Role of Practical Relevance between Instructional Practices of Teachers and Sustainable Engagement among Accounting Students in Saudi Arabia: The Moderating Role of Artificial Intelligence Usage - Alsheikh, Warda Hodaed (Journal of Economic, Administrative and Legal Sciences, 2025)
This research aimed to examine the direct influence of the instructional practices of teachers (IPT) on the sustainable engagement (SE) of accounting students studying in Saudi Arabian private and public universities. The study also aimed to investigate the mediating role of practical relevance (PR) in the above relationship. Furthermore, the study investigated whether artificial intelligence usage (AIU) by students has any moderating role in the above relationships. This study adopted a quantitative approach. Using the simple random sampling method, the study collected 374 responses for the analysis through the PLS-SEM. The results indicate that IPT does not necessarily influence sustainable engagement directly unless there is an indirect role of practical relevance. Surprisingly, the study didn’t find a moderating role for AIU in the above relationships. The results have practical implications for practitioners, managers, policymakers in to ignite sustainable engagement among the accounting students in Saudi Arabia and beyond.
Keywords: Instructional Practices of Teachers; Sustainable Engagement; Practical Relevance; Artificial Intelligence Usage; Accounting students; Saudi Arabia